العبور وتأنيث القوى في معلقة لبيد "مقاطع مختارة" - بن ضحوى, خيرة (roa; Vol 2 (2021): مجلة رؤى في الآداب والعلوم الإنسانية, 2021)
سنحاول في هذا البحث تتبع الفضاء المكاني المستخدم في القصيدة العربية قبل الإسلام، مركزين على مقاطع ثلاث من معلقة لبيد والتي مثل فيها الحيوان العنصر الأساس والتي نفترض تصور فلسفة العربي قديما حول قضايا الوجود، والموت والحياة وعلاقة الإنسان بالمكان وبمن حوله، وللحصول على نتائج تقريبية سنعتمد على مقاربة هذه المقاطع وفق ما جاءت به نظرية فان جانب حول طقس العبور محددين بذلك لحظات الانفصال ومراحل الهامش والاتصال بعد ذلك داخل القصيدة، التي تعد خطابا موازيا يأخذ من الواقع ويتجاوزه بالمجاز، فتكون الصور الحيوان ماهي إلا خطابات تتضاعف كلما اقتربنا منها تأويلا. الكلمات المفتاحية: خطاب، الشّعر الجاهلي، الحيوان، فضاء، زمان، طقس. Abstract:       In this research we will try to trace the spatial space used in the pre-Islamic Arabic poem, focusing on three syllables from labid odes, in which the animal represented the basic element, and in which we suppose the ancient Arab philosophy depicts the issues of existence, death, life and the relationship of man to the place and those around it, and to obtain approximate results we will adopt On approaching these passages according to what was presented by a theory, there is an aspect about the rite of passage, determining the moments of separation and the stages of the margin and contact after that within the poem which is a parallel discourse that takes from reality and transcends it metaphorically, so that the animal images are nothing but letters that multiply as we approach them with interpretation. Key words : discourse, pre-Islamic poetry, animal, space, time, ritual.